SPE Annual Technical Conference and Exhibition 2000
DOI: 10.2118/63049-ms
|View full text |Cite
|
Sign up to set email alerts
|

Hole Cleaning Capabilities of Drilling Foams Compared to Conventional Fluids

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractThis paper provides a comprehensive analysis of hole cleaning with drilling foam and conventional drilling fluids in inclined wells using a fluid mechanics approach without inertial effect. A simple experimental set-up was designed to study hole cleaning properties of various drilling fluids. Foams with controlled quality were generated and accurately characterized from a rheometrical point of view. These foams behave like shear thinning yield stress fluids a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…It provides an experimental basis methodology for the simple evaluation of carrying capacity of any kind of drilling fluids in a deviated wellbore. This experimental methodology will be developed for more comprehensive studies of hole cleaning problematic 13,14 . …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It provides an experimental basis methodology for the simple evaluation of carrying capacity of any kind of drilling fluids in a deviated wellbore. This experimental methodology will be developed for more comprehensive studies of hole cleaning problematic 13,14 . …”
Section: Resultsmentioning
confidence: 99%
“…This approach is mainly phenomenological and more comprehensive studies will be found elsewhere 13,14 .…”
Section: Carrying Capacity Of Foamsmentioning
confidence: 99%
“…It is used to lower the surface tension between the gas and the base fluid [4]. Saintpere et al [5] reported that foam rehology follow the Herschel Bulkley viscosity model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, studies conducted on cuttings transport with aerated fluids, especially with foams, for high inclination wells are very limited. Saintpere et al (2000) analyzed the hole cleaning with foam in inclined wells using a fluid mechanics approach ignoring the inertial effects. They introduced a few dimensionless parameters for describing the fluid rheology, foam properties, flowing time, etc.…”
Section: Literature Reviewmentioning
confidence: 99%